Sense of Belonging and Environmental Awareness Among Tourism Community Youth: Rasa Keterikatan dan Kesadaran Lingkungan di Kalangan Pemuda Komunitas Pariwisata - Tunggal Arys Saputra; Ghozali Rusyid Affandi (Academia Open, 2025)
General Background: Environmental awareness is a fundamental component in maintaining ecological sustainability and supporting responsible community-based tourism development. Specific Background: Local youth participation is considered essential in preserving natural tourism destinations, particularly in rural communities that rely on environmental resources for socio-economic development. Knowledge Gap: Despite the recognized importance of community attachment, empirical research examining the relationship between sense of belonging and environmental awareness among youth in tourism-based rural settings remains limited. Aims: This study aimed to examine the relationship between sense of belonging and environmental awareness among youth in Gunung Petung Hamlet, Tutur Village, Pasuruan Regency, within the development of Sumber Nyonya waterfall tourism. Results: Using a quantitative correlational design involving 172 respondents selected through accidental sampling, data were collected using sense of belonging and environmental awareness scales and analyzed using simple linear regression. The findings revealed a statistically significant relationship between sense of belonging and environmental awareness (F = 16.700, p < .001). The model summary indicated an R value of 0.299 and R² value of 0.089, demonstrating that sense of belonging accounts for 8.9% of environmental awareness variance, while 91.1% is explained by other variables outside the study. Novelty: This study provides empirical evidence linking community attachment with environmental awareness among rural tourism youth populations. Implications: The findings highlight the importance of strengthening community attachment initiatives to encourage youth participation in environmental preservation and sustainable nature-based tourism development. Highlights: Community Attachment Explains 8.9% Variation in Ecological Responsibility Levels. Statistical Testing Confirms a Significant Association Between Social Attachment and Conservation Understanding. Empirical Data Support Youth Involvement in Nature Destination Preservation Programs. Keywords: Sense of Belonging, Environmental Awareness, Youth Participation, Community Tourism, Rural Tourism